Methodological Considerations for TMD Research: A Call for More Robust Assessment and Analysis [Letter] - Zhang C; Shi K; Zheng Y (Journal of Pain Research)
Chengqi Zhang,1 Keying Shi,2 Yuanna Zheng3 1Stomatology Grade 2022, School/Hospital of Stomatology, Zhejiang Chinese Medical University, Hangzhou, 310053, People’s Republic of China; 2Ningbo Dental Hospital/Ningbo Oral Health Research Institute, Ningbo, People’s Republic of China; 3School/Hospital of Stomatology, Zhejiang Chinese Medical University, Hangzhou 310053, People’s Republic of China; Ningbo Dental Hospital/Ningbo Oral Health Research Institute, Ningbo, People’s Republic of ChinaCorrespondence: Yuanna Zheng, Email zyn218@126.com